Pengaruh Pemberian Kompos Sampah Rumah Tangga Terhadap Pertumbuhan Chlorella vulgaris Pada Skala Laboratorium - Hafizhah, Reka; Hariyati, Riche (Bioma : Berkala Ilmiah Biologi, 2012)
Accumulation household organic waste caused environtment disturbances such as bad odor, methan occur, stoppage canal water, and disease spread. Organic waste processing are needed in order to reduce this problem. Processing household waste into composs was one way to reduce organic waste accumulation. The objective of this study is to determine optimal dose household composs for Chlorella vulgaris growth. Research are done in two phase within 9 days of each. Composs liquid doses for main research are 6%,7%,8%, 10%, and Walne fertilizer used as control. Result show effect of household composs on Chlorella vulgaris growth. Optimal doses for Chlorella vulgaris growth are composs liquid dosesÂ  8% and 10%. Â  Key word: Household composs, Growth, Chlorella vulgaris.